2022
DOI: 10.1186/s13045-022-01258-8
|View full text |Cite
|
Sign up to set email alerts
|

A proteolysis-targeting chimera molecule selectively degrades ENL and inhibits malignant gene expression and tumor growth

Abstract: Background Chromosome translocations involving mixed lineage leukemia 1 (MLL1) cause acute leukemia in most infants and 5–10% children/adults with dismal clinical outcomes. Most frequent MLL1-fusion partners AF4/AFF4, AF9/ENL and ELL, together with CDK9/cyclin-T1, constitute super elongation complexes (SEC), which promote aberrant gene transcription, oncogenesis and maintenance of MLL1-rearranged (MLL1-r) leukemia. Notably, ENL, but not its paralog AF9, is essential for MLL1-r leukemia (and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Compared to other cancer cells, renal cancer cells and leukemia cells are more susceptible to clearance. Some studies on leukemia have shown that targeted therapy has a positive effect on the treatment of leukemia [ 62 , 63 ], so our future research may be extended in the direction of leukemia treatment. However, it is important to note that the present study has limitations, primarily related to the use of transcriptome sequencing data and the relatively small sample size of single-cell data.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other cancer cells, renal cancer cells and leukemia cells are more susceptible to clearance. Some studies on leukemia have shown that targeted therapy has a positive effect on the treatment of leukemia [ 62 , 63 ], so our future research may be extended in the direction of leukemia treatment. However, it is important to note that the present study has limitations, primarily related to the use of transcriptome sequencing data and the relatively small sample size of single-cell data.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Li et al. 143 developed novel PROTAC 69 and HyT degrader 70 targeting ENL by linking the YEATS inhibitor SGC-iMLLT 68 with thalidomide or hydrophobic tagging. PROTAC 69 efficiently degraded ENL in MV4; 11 leukemia cells, exhibiting a DC 50 of 37 nmol/L and almost complete depletion at ∼500 nmol/L ( D max ∼95%) ( Fig.…”
Section: Enl-targeting Degradersmentioning
confidence: 99%
“…13). 168 Briefly, compound 1 displayed DC 50 of 37 nM and 44 nM in MV4;11 and MOLM13 cell lines, respectively. Furthermore, the degradation of ENL by compound 1 is mediated through the UPS pathway and can be rescued with either the parent inhibitor itself and thalidomide and proteosome inhibitor bortezomib.…”
Section: Enl Degradersmentioning
confidence: 99%